2019
DOI: 10.1016/j.pedneo.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of hemolytic uremic syndrome in southern Romania during 2015–2016: Epidemiologic, clinical, laboratory, microbiologic, therapeutic and outcome characteristics

Abstract: The principal STEC serotype involved was O:H and the number of confirmed HUS cases reached half of the patients. Compared with the medical literature, this outbreak had a higher rate of complications and renal sequelae and was associated with a high fatality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
3
0
3
Order By: Relevance
“…Hemolytic uremic syndrome (HUS) is described as a multisystemic disease 6,7 that affects mainly the kidney and is a major cause of morbidity and mortality in children under the age of 5 years old 1 . The kidney and brain are the main target organs affected in patients with HUS 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Hemolytic uremic syndrome (HUS) is described as a multisystemic disease 6,7 that affects mainly the kidney and is a major cause of morbidity and mortality in children under the age of 5 years old 1 . The kidney and brain are the main target organs affected in patients with HUS 2 .…”
Section: Discussionmentioning
confidence: 99%
“…This form of culture medium had been in limited use in New Zealand laboratories. However, the advent of nucleic acid amplification technology and toxin enzyme immunoassays has demonstrated that non-O157:H7 STEC serotypes can also cause HUS [11][12][13][14]. STEC-HUS is a common cause of acute kidney injury (AKI) in children requiring acute kidney replacement therapy in developed countries [15][16][17].…”
Section: Methodsmentioning
confidence: 99%
“…Bizim çalışma grubumuzun ortanca yaşı literatür ile uyumlu olup 18 ay olarak hesaplandı (Tablo 1). Diyare ilişkili HÜS için cinsler arasında bir fark tanımlanmamıştır (2)(3)(4)(5)(6)(7)(8)11,(15)(16)(17)(18)(19). Çalışmamızda 9 (%60) erkek hasta olup cinsler arasında anlamlı fark görülmedi.…”
Section: Bulgularunclassified
“…Literatür ile uyumlu olarak hastalarımızın %60'ında BYKT ihtiyacı gözlendi (7,11,18,20,21,26,27). Diyare ilişkili HÜS hastalarında ortalama BYKT tedavisi süreleri 10-18,5 gün aralığında olduğu bildirilmektedir (1,7,8,17,18,21). Bizim çalışmamızda da ortalama BYKT süresi literatür ile uyumlu olup, 15,11±9,11 gün olarak hesaplandı.…”
Section: Bulgularunclassified
See 1 more Smart Citation